FUNGICIDAL AND INHIBITORY EFFECTS OF OF MONARDA FISTULOSA ESSENTIAL OIL AND EUGENOL AGAINST FUNGI OF ASPERGILLUS GENUS - Кinash, О.V.; Lisachenko, О.D.; Kupriyan, К.V. (World of Medicine and Biology, 2018)
The Aspergillus genus fungi most frequently cause pathological processes in individuals with immunodeficiency and in those who are in prolonged contact with high concentrations of spores. The suggested means of controlling contamination with pathogenic micromycetes are, as a rule, dangerous for the environment. The present paper submits the results of studying fungicidal and fungistatic properties of plant origin substances: essential oils of horsemint (Monarda) and eugenol. To achieve the purpose, standard methods of agar-gel diffusion were used. Іt was determined that the substances under study actually possessed a spectrum of fungicidal and fungistatic properties, which were manifested by the growth retardation and developmental phase disorders in the fungi cultures of Aspergillus fumigatus, Aspergillus flavus and Aspergillus niger. Fungistatic action of monarda and eugenol essential oils was characterized by the absence of pigmentation and conidia genesis, weak development of vegetative mycelium of test cultures. At the second stage, determination of the minimum depressant concentration (MPC) in the essential oils of monarda and eugenol in relation to the studied fungi cultures was performed. It was established that fungicidal and fungistatic properties of eugenol are found at lower concentrations in comparison with the monarda essential oil. The study results can be used to develop environmentally friendly means of optimizing air or disinfectants.
Keywords: essential oil of monarchy tubular; eugenol; Aspergillus fumigatus; Aspergillus flavus; Aspergillus niger